The Influence of Mother Figure on the Thoughts of Students in Class XII at SMA PGRI 1 Lumajang Indonesia - Bopel Wasianto; Eka Ismaya Indra Purnamanita; Imam Syaifudin; Ahmad Yusthru Daswara; Rahmaniawati Rahmaniawati (Journal of Social Research, 2022)
In family life, a mother has a very big role in children's education, therefore the mother is a madrasatul hall for her children. The mother figure acts as a "role model" or role model for children, adolescents, and adults. Regarding the importance of a good mother figure, the researcher is interested in examining the influence of a mother figure on the morals of class XII students at SMA PGRI 1 Lumajang in the 2022/2023 academic year. Based on the background above, the discussion issues that can be taken are: 1) Is there any influence of the mother figure on the morals of class XII students at SMA PGRI 1 Lumajang in the 2022/2023 academic year? 2) How much influence does the mother figure have on the morals of class XII students at SMA PGRI 1 Lumajang in the 2022/2023 academic year? The aims of this study were: 1) To find out the influence of the mother figure on the morals of class XII students at SMA PGRI 1 Lumajang in the 2022/2023 academic year. 2) Describe how much influence the mother figure has on the morals of class XII students at SMA PGRI 1 Lumajang in the 2022/2023 academic year. The benefits of research are that it can make a theoretical contribution to science, especially with regard to the influence of the mother figure on the morals of students. The method used in this research is to use quantitative statistical research methods and use several data collection methods, namely observation, questionnaires, interviews, and documentation.